POLYMERS RECYCLING: UPCYCLING TECHNIQUES. AN OVERVIEW - Martina Zúñiga D; Francisca L. Aranda; Bernabe L Rivas (Journal of the Chilean Chemical Society, 2023)
Since 1950 plastics became the materials of greatest world production. Thus, in recent years the increase in the use of different types of plastics has been a matter of global concern due to the depletion of fossil fuels and the accumulation of waste in the different environmental matrices, affecting the ecosystem. By 2015, 4.9 million metric tons of plastic waste were recorded in landfills, because more than 40% of the plastics produced are designed for single use. The mass amount of plastic is estimated to exceed 450 million tonnes per year and will double by 2045.Due to the great problem of plastics and their threats to the ecosystem, the researchers worked on a large number of technologies to mitigate the effect of plastics on the different environmental matrices. Therefore, the main goal of this manuscript is summarizes on the plastics more used as well as the most common techniques to reduce their presence at the environment.